HOLISTIC WATER MINIMISATION - Zainuddin Abdul Manan; Sharifah Rafidah Wan Alwi (PERINTIS eJournal, 2021)
Water is a vital resource to mankind. Many religions regard a person’s attitude towards conservation of resources, namely water, as an indication of her faith. The Holy Quran says (Al-Araf, 31), “But waste not by excess: for Allah loveth not the wasters”. Sustainable management of water resources entails the use of a systems approach because educating to change public attitudes is not expected to result in a high degree of domestic water saving. This contribution describes a framework for holistic water minimisation that was applied to Sultan Ismail Mosque in Universiti Teknologi Malaysia (UTM). The framework employs a systems approach that revolves around the hierarchy of water management to maximise water savings